Anatomical limits on interaural time differences: an ecological perspective - HARTMANN, WILLIAM M.; Macaulay, Eric J. (Frontiers in Neuroscience, 2014)
Human listeners, and other animals too, use interaural time differences (ITD) to localize sounds. If the sounds are pure tones, a simple frequency factor relates the ITD to the interaural phase difference (IPD), for which there are known iso-IPD boundaries, 90$^°$, 180$^°$~… defining regions of spatial perception. In this article, iso-IPD boundaries for humans are translated into azimuths using a spherical head model, and the calculations are checked by free-field measurements. The translated boundaries provide quantitative tests of an ecological interpretation for the dramatic onset of ITD insensitivity at high frequencies. According to this interpretation, the insensitivity serves as a defense against misinformation and can be attributed to limits on binaural processing in the brainstem. Calculations show that the ecological explanation passes the tests only if the binaural brainstem properties evolved or developed consistent with heads that are 50% smaller than current adult heads. Measurements on more realistic head shapes relax that requirement only slightly. The problem posed by the discrepancy between the current head size and a smaller, ideal head size was apparently solved by the evolution or development of central processes that discount large IPDs in favor of interaural level differences. The latter become more important with increasing head size.